KAJIAN DAMPAK LA NINA TERHADAP KUALITAS HASIL SALAK PONDOH (Salacca edulis Reinw.) SELAMA PENYIMPANAN SUHU RUANG - N Nasrudin; Prahesti Elizani (Fapetrik-UMPAR, 2019)
Changes in rainfall with high humidity due to La Nina can be one of the factors that can affect the quality of the yield of horticultural products. La Nina simulation was done by soaking snake fruits in water for a certain time. The aimed of this research was to examine the effect of La Nina carried out using simulations on several quality parameters of snake fruits. This research used a non-factorial Completely Randomized Design (CRD) with two treatments, fruit without soaking and fruit soaked for 5 minutes (La Nina simulation). The treatment was repeated three times. Observations were made at 0 days, 3 days, 6 days and 9 days. The La Nina simulation treatment with 5 minutes soaking affected the quality of snake fruits, which shown by the decreasing in the physical appearance of the fruit, the hardness of the fruit, and the total acid content of the fruit. In general, a decrease in some qualities of snake fruits occurs on the 6th to 9th day of storage.